Design project for upgrading the technological equipment of a loader with the addition of a grapple attachment: master's qualification work - Hamza, Samir (Харківський національний автомобільно-дорожній університет, 2024)
The object of the project is a specialized cargo-handling complex based on a 10-ton gantry crane. Project Objective: Mechanization of loading and unloading of log stacks using the newly created technological equipment powered by the power unit of the base tractor. The research method is analytical and graphic. The diploma project includes documentation for the development of a tracked loading machine. It outlines the initial design requirements, formulates technical task requirements, defines design input data, justifies grapple attachment parameters, and provides functional, hydraulic, and schematic diagrams of the machine. Additionally, the project covers the design of assembled units and parts, discusses the organization of work using the loading machine, as well as its operation and occupational safety. Economic benefits from the use of the designed machine have also been calculated.
Keywords: tractor; grapple attachment; loading; log stacks; efficiency